Prediction Of Cutting Force In End Milling Of Inconel 718 - Kasim, Mohd Shahir; Raja Abdullah, Raja Izamshah; Minhat, Mohamad; Mohamad, Noraiham; Che Haron, Che Hassan; A Ghani, Jaharah; Saedon, Juri; Saad, Nor Hayati; Mohamed, Saiful Bahri (Penerbit Universiti Teknikal Malaysia Melaka, 2014)
This paper presents the effect of cutting parameters on the cutting force when machining Inconel 718. Response surface methodology (RSM) was used in the experiment, and a Box–Behnken design was employed to identify the cause and effect of the relationship between the four cutting parameters (cutting speed, feed rate, depth of cut and width of cut) and cutting force. The ball-nose type of end mill with donwmill approach was maitained througout the experiment. The forces were measured using kistler dynamometer during straight line machining strategy. The result shows that the radial depth of cut was the dominating factor controlling cutting force, it was followed by axial depth of cut and feed rate. The prediction cutting force model was developed with the average error between the predicted and actual cutting force was less than 3%.